Heavy Grazing Altered the Biodiversity–Productivity Relationship of Alpine Grasslands in Lhasa River Valley, Tibet - Xiang, Mingxue; Wu, Junxi; Wu, Jiaojiao; Guo, Yingjie; Lha, Duo; Pan, Ying; Zhang, Xianzhou (Frontiers in Ecology and Evolution, 2021)
Grazing is a crucial anthropogenic disturbance on grasslands. However, it is unknown how livestock grazing affects the relationship between biodiversity and productivity of alpine grasslands in Tibet. We carried out a grazing-manipulated experiment from 2016 to 2019 with grazing intensity levels of null (control, grazing exclusion, C.K.), moderate grazing (1.65 standardized sheep unit (SSU) per hectare, M.G.), and heavy grazing (2.47 SSU per hectare, H.G.) on a typical alpine grassland in the Lhasa River Basin, Central Tibet. We measured aboveground biomass (AGB), species assembly (alpha- and beta-diversity indices), and soil nutrients’ availability. The results showed that grazing differently affected plant community in different treatments. Notably, the total dissimilarity value between C.K. and H.G is 0.334. Grazing decreased the Shannon-Weiner index, increased the Berger-Parker index from 2016 to 2018 significantly, and decreased AGB and total soil nitrogen (STN) significantly. Our results also showed that the grazing affected the relationship between AGB and diversity indices and soil nutrients, including soil organic carbon (SOC), and total soil phosphorus (STP). Specifically, AGB decreased with increasing SOC and STP in all treatments, and heavy grazing changed the positive relationships between AGB, STP, and Shannon-Weiner index to negative correlations significantly compared with grazing exclusion. There was a significant negative correlation between Berger-Parker and Shannon-Weiner indices under each treatment. The general linear models showed that H.G. altered the relationship between diversity and productivity of grassland in Central Tibetan, AGB and Shannon-Weiner index positively correlated in C.K. but that of negatively correlated in H.G. Our study suggests that H.G. caused a negative relationship between plant diversity and productivity. Therefore, sustainable grazing management calls to need a better understanding the relationship between biodiversity and productivity of alpine grassland in Central Tibet.